Estrutura e propriedade fotoluminescente do titanato de bário e cálcio obtido pelo método de polimerização de complexos (MPC) - Motta, Fabiana Villela da (2008)
The synthesis and characterization of Ba1-xCaxTiO3 (BCT) for x = 5; 10; 15; 20; 40 e 80 % mol that crystallizes in a perovisquita structure were studied in this work. The BCT material was synthesized by CPM which allows obtaining structurally ordered and disordered powders. The effect of the calcium concentration was analyzed for the structurally ordered and disordered materials. The powders were crystallized at several temperatures ranging from 400 to 1200 °C for different times. The obtained materials were characterized by X-ray diffraction (XRD), Raman spectroscopy, differential scanning calorimetry (DSC) and X-ray Absorption Near Edge Structure (XANES) and photoluminescent emission (PL). These techniques allowed to observe the evolution of the phases as well as the structural disorder of the samples. XRD results indicated that up to 20 % mol of calcium, there is formation of a solid solution with Ca2+ ion occupying the Ba2+ site in the of the BaTiO3 crystalline network. It was verified that the BCT ordered phase was obtained after calcining at 600 °C by 2 h. The presence of an intermediate oxicarbonate barium phase in temperatures below of the tetragonal BCT crystallization. The luminescent property of structurally ordered and disordered BCT powders were studied at room temperature, using two excitation wavelengths: 350,7 nm and 488,0 nm. Structurally disordered BCT present broad PL band when excited by both of wavelengths. The powders annealed at 500 oC displays the most significant PL intensity. It was verified that with the increase of the calcium concentration, the maximum of the photoluminescent emission curve tends to laser wavelength energy. XANES spectra showed in the disordered powders the coexistence of sixfold and fivefold titanium coordination. A correlation between the coexistence of this two types of coordination for the titanium atoms and PL was proposed.